IDENTITAS VISUAL DALAM PERANCANGAN MEDIA PROMOSI MUSEUM MELANGE KARANGSAMBUNG, KEBUMEN - Nur Hamidatur Rohmah; Pandanwangi, Brilindra (Institut Bisnis dan Teknologi Indonesia, 2023)
Museum Melange has an absence of the definitive and representative visual identity as an earth conservation place with a diverse collection of national and international scaled geological heritage sites (Geo sites), which has resulted in the inability to represent its identity that makes it different from other museums. Therefore, it is necessary to design a visual identity in order to build and strengthen the identity of the Melange Karangsambung Museum, Kebumen. In this creation method, it uses the design thinking process which starts with data collection (literature studies, observations, and interviews). This design produces a visual identity that is used in promotional media with the AISAS (Attention, Interest, Search, Action, and, Share) strategy. The promotional medium that this creation uses are Instagram social media and other media such as: stone samples for educational purpose, wristbands, uniform organizers, stationery items, and merchandise to attract the general public to visit the Melange Museum.